Microbe Foiled Again/Recipe for success: Prepare & serve food safely - Clark, Mary P.; Peters, Paula; Grover, Phyllis (My University, 1994)
Microbe Foiled Again/Recipe for success: Prepare & serve food safely is the third in a five-part program on Safe Food for Children: A series of lessons for parents and child care providers.
L894_1994-11
Keywords: L894; Home and Family; Health and Safety; L